Інституційні ефекти розвитку інтегрованих структур - Данкевич, Андрій Євгенович (My University, 2010)
Досліджено ефективність роботи агрохолдингів, висвітлено їх переваги й недоліки та науково обґрунтовано рекомендації щодо перспектив подальшого розвитку. Агрохолдинги формуються, як правило, на основі провідної компанії, орендують землю одночасно в багатьох регіонах. За попередніми оцінками в Україні функціонує понад 60 великих холдингів, більшість з яких не виділені в окремий бізнес

The effectiveness of the work of agricultural holdings was studied, their advantages and disadvantages were highlighted, and recommendations regarding the prospects for further development were scientifically substantiated. Agricultural holdings are formed, as a rule, on the basis of a leading company, lease land simultaneously in many regions. According to preliminary estimates, more than 60 large holdings operate in Ukraine, most of which are not separated into separate businesses
Keywords: кафедра економіки і права; інституції; агрохолдинг; ефективність; інтеграція; конкурентоспроможність; капітал; менеджмент; диверсифікація; institutions; agricultural holding; efficiency; integration; competitiveness; capital; management; diversification